Revestimento cerâmico em fachadas - o contributo do desenho e fabricação digital - Rita Salomé Magano Bastião (2019)
The present dissertation seeks to investigate and analyze how the use of new digital technologies influences the design of ceramics in architecture, specifically as facade cladding. Firstly, it is intended the understanding of the possibilities, properties and nature of ceramics and its evolution over time. Consequently the manufacturing processes and the technical specificities inherent to the choice of this material in the architectural design are also studied. As case studies, three examples of contemporary architecture in Portugal are used where the design of the ceramic pieces is fundamental in the characterization of the building. They are the Porto Cruise Terminal, the Lisbon Aquarium extension and the Museum of Art, Architecture and Technology, in Lisbon as well. Reflecting on the contribution of new digital processes in architecture is the foundation for a practical and creative experience that culminates in the digital exploration of the ceramic cladding pieces of the studied buildings.